Pemanfaatan Ekstrak Kulit Singkong Dan Air Cucian Beras Pada Pertumbuhan Tanaman Sirsak (Annona muricata L.) - Hikmah, Novia, Dra. Suparti M. Si (2015)
The growth and development of the plant soursop require nutrien elements that usually comes from synthetic chemical or organic. Water washing rice contains phosphorus, nitrogen, vitamins B1 and cassava peels extract contains carbon, nitrogen and sulfur can be used as an extra nutrients for the plant soursop. This purpose of reseach to determine the influence of the type of watering and concentration water washing rice and cassava peesl extract on the growth of the pland soursop ( Annoma muricata L.). The reseach contains of 2 factors, the first factor is the type of watering that is made up of water washing rice and cassava peels extract and the second factor is the concentration, namely 50 %, 755 and 100%. Treatment without water washing rice and cassava peels extract acts as a control. The reseach showed the best results is a mixture of water washing rice and cassava peels extract concentration of high growth stem 3,90 cm, number of leaves 1,66 (5 leaves) and length of the rood 2,30 cm of the plant soursop.